Effect of Explicit Teaching of Vocabulary Strategies on EFL Learners’ Recall and Recognition of Academic Words - Al Awabdeh, Abdelhameed; Albashtawi , Abeer Hameed; Mahfoodh, Omer Hassan Ali (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aimed at investigating the effect of the explicit teaching of vocabulary strategies on 202 EFL learners’ improvement of receptive vocabulary knowledge in terms of meaning recall and recognition of academic words. Methods: This mixed-methods study consisted of two phases: quantitative and qualitative. In the first phase which was a quasi-experimental design with two groups (experimental and control), all students responded to an adapted vocabulary test that has multiple choice and multiple matching questions. Through focus group interviews with some participants in the experimental group, qualitative data on students’ perceptions of the effectiveness of explicit teaching of vocabulary strategies were collected. While the quantitative data were analysed using descriptive statistics and Analysis of Covariance (ANCOVA), the interviews were transcribed and analysed thematically. Results: The results of the study revealed that the explicit method of teaching vocabulary strategies was effective in improving students’ vocabulary knowledge in terms of both meaning recall and recognition of academic words. Conclusions: Thus, the explicit method of teaching vocabulary strategies can be recommended for EFL learners in academic reading courses.